Bond Market Transparency and Stock Price Crash Risk: Evidence from a Natural Experiment - Guan, Yuyan; Kim, Jeong-Bon; Liu, Boluo; Xin, Xiangang (The Accounting Review, 2023)
ABSTRACT Utilizing the Trade Reporting and Compliance Engine (TRACE) setting as an exogenous shock to bond market transparency, we find that improved bond market transparency leads to lower crash risk in the stock market, consistent with increased information spillover from the bond market into the stock market. Results from the Path analysis suggest that bond market transparency affects stock price crash risk not only directly, but also indirectly through its effects on management guidance, analyst forecasts, and media reports. We also find that the mitigation effect of bond market transparency on stock price crash risk is more pronounced for firms with higher default risk bonds, lower institutional stock ownership, and more opaque financial reporting. Overall, our findings suggest that increased bond market transparency following TRACE generates a positive externality in reducing crash risk in the stock market. JEL Classifications: D83; G14; G24.